Evaluating the use of concentric circular plots and mark-recapture techniques for estimating pipefish population size in a coastal marine seagrass bed - Sims, Megan (My University, 2024)
Concentric circular plots are widely used in terrestrial environments but are underutilized in marine environments. We tested the feasibility of using this method coupled with mark-resight and recapture designs within a Tampa Bay coastal marine seagrass bed. Two circular, 20-m diameter sites with four rings each were sampled during each event to collect adult Gulf pipefish, Syngnathus scovelli, a flagship species for seagrass ecosystems. In August 2022, we conducted a mark-resight experiment with 7 sampling events that collected 2,065 adult pipefish (802 individuals marked) and registered 246 recaptures (193 distinct fish). Although the population surveyed was male biased, more females were recaptured. Additionally, recaptured males disproportionally moved within the sites and were repeatedly recaptured. The immigration-emigration mixed logit-normal Mark model could not converge due to its sensitive parameters but suggested a residential superpopulation. In February 2023, we conducted a standard mark-recapture with 6 sampling events that collected 194 adult pipefish (187 individuals) and registered 6 recaptures (5 distinct fish). The POPAN Mark model estimated a superpopulation of 1,967 fish surrounding our sites and indicated a transient superpopulation. Repeated sampling disturbance within the sites had no significant impact on fish densities, but the seagrass habitat experienced significant negative effects. Data collected using concentric circular plots and linear transects during this study were similar. Therefore, our results indicate concentric circular plots are feasible in coastal marine environments and can be coupled with marking techniques to elucidate movement patterns and habitat use, but future use of this methodology should monitor habitat sampling effects.
Keywords: Biology; Biology; Aquatic sciences; Gulf pipefish; Marine animals; Marine biology--Research; Habitat (Ecology); Fish populations; Biological monitoring; Marine habitats; Environmental impact analysis; Ecological surveys; Tampa Bay (Fla.); Gulf of Mexico--Tampa Bay; Florida; Academic theses